Drug abuse among public high school students in Cebu City - Anderson, Rosalie (Duran),1938- (s.n.], 1972)
This study attempted to discover the extent of drug use among public high school students of Cebu City, and also endeavored to compare drug users and non-drug users on several variables. The survey method was used with a questionnaire devised by the writer as the major tool. A two-stage sampling design was used. The questionnaire was administered to 1166 students. Findings of the study include the percentage of the students using drugs, their reasons for using, the drugs used, and the attitude among students towards drugs.